Behind the Comments: Analyzing Netizen Responses to IShowSpeed’s Indonesia Visit - Nurpratama, Muhammad Rifky (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2025)
In 2023, there will be more than 212 million internet users in Indonesia, making social media a vital forum for public communication, including participation in international cultural events. International celebrity IShowSpeed's 2024 visit to Indonesia generated a lot of conversation on social media, especially on Instagram with the handle @folkative. This study aims to analyze netizens’ responses to this visit using a qualitative content analysis approach, examining viral comments to reveal patterns of sentiment, humor, sarcasm, and cultural identity expressed by Indonesian netizens. The findings indicate that netizens’ responses reflect not only admiration or criticism of IShowSpeed but also serve as a medium to express national identity and views on local social and cultural issues. This study provides an in-depth understanding of how global pop culture influences communication dynamics on social media, highlighting the significance of social media as a digital public space that facilitates cross-cultural interaction.